Does Social Media Advertising Features Matter An Investigation of Consumer Purchase Intention - Shah, Hafiz Wajahat Ali; Khan, Imran; Hameed, Abdul (iRASD Journal of Management, 2019)
Social media is continuously used as a platform for marketing and advertising. Firms have spent a lot of seasons, cash and property on Social media ads. However, it is all the time stimulating how Firms can prepare Social media advertising to fortunately engage and inspire a consumer to purchase their brands. The purpose of this research is consequently to describe and check the key elements of Social media advertising that force anticipate the buy intention. The theoretical model was expected on the foundation of three factors from the expansion of the Unified Theory Acceptance and Use of Technology (UTAUT2) (Performance expectancy, Hedonic motivation and Habit) along with Interactivity, Informativeness and Perceived relevance. The data was composed using a questionnaire survey of 260 participants. The most important results of structural equation modelling (SEM) mainly sustained the validity of the current model and the significant impact of Performance expectancy, Hedonic motivation and Interactivity, Informativeness, and Perceived relevance on purchase intentions. Confidently, this study will produce a set of theoretical and practical instruction on how marketers can successfully plan and apply their ads through Social media platforms.